Sanksi Adat pada Lembaga Perkreditan Desa dalam Kerangka Principal-Agent LPD (Lembaga perkreditan Desa) Se-Kecamatan Tembuku, Kabupaten Bangli - Kartika, Nengah; Jember, I Made (Jurnal Ekonomi Kuantitatif Terapan, 2017)
LPD is a form of non-formal financial institution whose role has becoming very important in Bali. As credit dealer, LPD has several problems regarding its debtor and creditor which causes non-performing loans. This study discusses the causes of credit, the impact of sanction and rules from Balinese traditional custom, differences in return on asset (ROA) between LPDs which applied traditional customs and rules in all LPDs on Tembuku districts. We used the principal-agent theory to determine the differences on ROA between LPDs who applies the traditional custom and those who do not. We found out that there’s differences between the two. This study also found out that the biggest impact of sanction from traditional customs to failing debtor are psychological pressure and embarrassment.
Keywords: Principal-agent; Sanksi dan aturan adat; Moral hazard; Rule of The Game; Kredit Macet